ACTIVE CHAT HEADS: A NETNOGRAPHY OF PROFESSIONAL TERTIARY TEACHERS - Cahapay, Michael B (PUPIL: International Journal of Teaching, Education and Learning, 2020)
The advancement of technology has brought professional learning into the online community of practice. However, the kind of culture in an online community of practice considered as informal has not been well explored. Hence, this paper described the culture of an informal community of practice of professional tertiary teachers in a private online group. Employing the traditional, personal participant observation techniques of anthropology to the study of culture manifesting through online communication, this study employed online ethnography or netnography. It involved observation and analysis of a small and intact group of five professional tertiary teachers. They share online communication of nine thousand two hundred seventy-two chat messages over a period in a private chat group. The results show that the interaction patterns in the online community are played by central characters and a hierarchy of shared activities constitute the culture of the online community. The members can take advantage of participating in their informal community of practice, and this time, in a more intentional manner. The activities are instructive and can be relevant in a work condition where time is constrained for face-to-face discussions.